Sexual and reproductive health and rights of Ashaninka women of the Ene River - Cavero M., Giovanna (2014)
The epidemic profile in our country shows a series of problems that affect mainly the health of women and that in most cases is a consequence of gender inequity and poverty. This together with a loss of their right to their sexuality, through control mechanisms and exercise of power which constrain their right to improve their quality of life and human development. Moreover, health policy makers do not respond to the necessities, problems and demands coming from the most remote and multicultural settlements. Therefore, its is necessary to know this people's reality before devising solutions by means of educational programs, the invigoration of sexual and reproductive rights of both women and men, as well as promoting the participation of health service professionals, from a gender perspective.